Geohazards Caused by Human Activity - Farid, Arvin (IntechOpen, 2016)
This book is based on the contributions of several authors and attempts to describe the roles human activities play in causing geohazards either directly or indirectly through man-made climate change. The risk of these man-made geohazards and the risk assessment are also discussed in this book. Each chapter keeps the authors' notations that vary from chapter to chapter. These authors' notations have been maintained to reduce unintended confusion and errors. Readers should be aware of this variation.